Understanding the motives behind the consumption of organic products in North Portugal: a focus group study - Penalba-Sánchez, Lucía; Di-Gregorio, Elisa; Claro, Raquel; Pinto, Mafalda; Pinto, Elisabete; Oliveira-Silva, Patrícia (Frontiers in Sustainable Food Systems, 2023)
The soil is a non-renewable and essential resource for life on our planet. Considering the widespread fast pace of soil degradation and erosion, it is urgent to protect it by enacting pro-environmental behaviours. Consumers' massive purchase and consumption of organic products is a powerful way to encourage farmers to apply sustainable soil practices. Unfortunately, there is a lack of studies in Portugal explaining the increased interest but low consumption of organic products. Here, the relationship between (a) intrinsic motivations, extrinsic motivations, knowledge, and self-perception of control regarding pro-environmental behaviours, and (b) consumption of organic products and other related pro-environmental behaviours was explored. To do so, two semi-structured interview focus groups (n = 15 participants) were conducted. Results indicated that organic product purchase and consumption seem to be driven by intrinsic motivations such as health or environmental concerns. External aspects such as labels and price as well, as personal, and psychological elements like knowledge and self-control, may be attenuating or strengthening the behaviour. These findings should be validated in quantitative studies.2 This is a provisional file, not the final typeset article For Original Research Articles, Clinical Trial Articles, and Technology Reports the introduction should be succinct, with no subheadings. For Case Reports the Introduction should include symptoms at presentation, physical exams, and lab results.